KERAGAMAN MAMALIA DISEKITAR DAERAH PENYANGGA TAMAN NASIONAL GUNUNG HALIMUN, KECAMATAN CIPANAS, KABUPATEN LEBAK - Agustinus Suyanto; Gono Semiadi (Research Center for Biology-Indonesian Institute of Sciences, 2004)
The fieldworks for inventory and collection on mammals in Gunung Halimun National Park (OHNP) had been carried out for long time; however the works only focused on the areas belong to Bogor District. Therefore, the fieldwork was carried out in the buffer zone of the GHNP in Lebak District.The fieldwork had collected 70 numbers consisted of 16 species of mammals, of which five species were new records for GHNP and of those five species, two species (Glischropus javanus and Myotis sp.)were new collection for the Museum Zoologicum Bogoriense-Research Center for Biology-The Indonesian Institute of Sciences (LIPI).The Baduy people were noticed to hunt fruit-bats from some caves for their food.It was suggested a monitoring activity on the utilization of fruit-bats should be conducted for the conservation of the fruit-bats.Further fieldwork outside the Bogor District in the future should also be considered, particularly on the area along the river.